The Methodological Heritage of Newton. - Butts, Robert, E. (Heritage., 1970)
The essays included in this volume are concerned with assessing Newton's contribution to the thought of others. They explore all aspects of the conceptual background-historical, philosophical, and narrowly methodological-and examine questions that developed in the wake of Newton's science.